Characterization of village chicken and egg marketing systems of Bure district, North-West Ethiopia - Moges, F.; Dessie, Tadelle (2010)
A study was conducted to assess the existing village chicken and egg marketing system of Bure district, North West Ethiopia. A participatory rural appraisal and a formal survey were used to collect all the relevant data, using a multistage sampling technique. Seven farmer kebeles (2 from high land, 3 from mid altitude and 2 from low land agro ecologies) and a total of 280 village chicken owner households were selected and considered for the study. In addition, 30 chicken and egg collectors (middle men) were interviewed using a structured questionnaire. All local and urban markets were visited once in a month in all seasons of the year. The result of the current study revealed that there was no any formal chicken and egg marketing operation in the study district. The result showed that 69.3% and 99.6% of interviewed village chicken owners involved in marketing of chicken and eggs, respectively. Producer-Consumer, Producer-Middle men, Producer-Retailer, Middle men- Retailer, Middle men-Consumer were the prevailing chicken and egg marketing channels of the study district. According to the result of the study village chicken owners traveled, on average, a distance of 5.5km and 15.9km to reach to nearby local markets and urban markets, respectively. It is identified that the majority (59.3%) of chicken owners used both hand carrying (hanging birds with a piece of stick) and carrying birds with bamboo-made containers to transport live birds to markets. The result of the current study revealed that the price of chicken and eggs showed variation between months of the year. The percentage increase in market prices of chicken products at holyday market days, as compared to ordinary market days was 19.2% for cocks, 15.3% hen, 24.2% for pullets/cockerels and 16% for eggs. Some of the major marketing problems identified in this study were: low supply of marketable chicken products, presence of only few/limited market out-lets and lack of appropriate marketing information. It is suggested that chicken and egg marketing of village chicken producers can be improved through development of market information system at farmer’s level and strengthening of agricultural extension services, through trainings and advisory services.